Properties of Cu/Fe-Mn and Cu/Fe-Cr Metal Matrix Composites Produced by Powder Metallurgy - Turhan, Huseyin; Ozel, Serkan (Walter de Gruyter Gmbh, 2009)
Ferro-manganese and ferro-chromium particles (FeMnp and FeCrp) were added to a copper matrix and examined for applications requiring wear resistance and rupture strength. Cu/FeMnp, Cu/FeCrp and Cu/FeMnp/FeCrp metal matrix composites (MMCs) were prepared using a powder metallurgy technique to get a homogeneous distribution of particles in controlled amounts. Powders were mixed, compacted, and sintered in a protective argon gas environment. In a wear test, the MMCs showed a favorable resistance to weight loss when pressed against a moving AISI 304 stainless steel wear plate. Rupture strength was determined using a standard transverse rupture test. Fractographs taken of wear and ruptured surfaces together with rupture strength measurements were correlated. with the amount and type of particle reinforcement and MMC hardness. The formation of Metal Carbide (MC) and Metal Oxide (MO) around reinforcing particles was also considered. Transverse rupture strength was found to decrease after exceeding a specific amount of reinforcement.
Keywords: Reinforced Aluminum; Wear; Deformation; Mechanism; Steel